Eksistensi badan hukum di Indonesia sebagai wadah dalam menunjang kehidupan manusia - Ibrahim,, Johnny (Pelita Harapan University, 2011)
Legal personality is known by different names but has the same meaning, e.g.: artificial personality, juridical personality or juristic personality. It refers to the characteristics of a non-human entity regarded by law to have the status of a person. Legal personality allows one or more natural persons to act as a single entity for legal purposes. They may sue and be sued, enter into contracts, incur debts, and have ownership over property. Some countries prohibit legal entities from holding human rights, while other countries permit artificial persons to enjoy protection from the state that are traditionally described as human rights. Legal personality exists in the Indonesian legal system, as it is exist in the modern countries.